2021
DOI: 10.1002/ccd.29753
|View full text |Cite
|
Sign up to set email alerts
|

Impact of anemia on short‐term outcomes after TAVR: A subgroup analysis from the BRAVO‐3 randomized trial

Abstract: Objectives: To determine the prognostic impact of anemia in patients randomized to bivalirudin or unfractionated heparin (UFH) during transcatheter aortic valve replacement (TAVR).Background: Whether the periprocedural use of bivalirudin as compared with UFH in anemic patients undergoing TAVR has an impact on outcomes remains unknown. Methods:The BRAVO-3 trial compared the use of bivalirudin versus UFH in 802 high risk patients undergoing transfemoral TAVR for severe symptomatic aortic stenosis.Patients were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 36 publications
(101 reference statements)
0
4
0
Order By: Relevance
“…The review included five multicenter and six single-center observational studies. A prospective design was reported in five studies [ 6 , 9 , 15 , 16 , 17 ]. All studies had a sample size of >100 anemic patients (range: 169–1335 patients).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The review included five multicenter and six single-center observational studies. A prospective design was reported in five studies [ 6 , 9 , 15 , 16 , 17 ]. All studies had a sample size of >100 anemic patients (range: 169–1335 patients).…”
Section: Resultsmentioning
confidence: 99%
“… Forest plots showing pre-procedural anemia and associated odds of 30-day transfusion ( a ), acute renal failure ( b ), 30-day mortality ( c ) and mid-term mortality ( d ) [ 6 , 9 , 10 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. Asterisk indicates reported adjusted odds ratio [ 10 , 16 , 21 ].…”
Section: Figurementioning
confidence: 99%
“…The reference Hgb values for defining anemia are largely based on the definition provided by the World Health Organization (WHO) in 1968 ( 9 ). The presence of underlying anemia is linked with poor outcomes in cardiac patients including coronary artery disease and congestive heart failure, patients undergoing transcatheter aortic valve replacement, and patients undergoing PCI including in-hospital and long-term adverse events ( 3 , 5 , 8 , 10 12 ). In the context of acute coronary syndrome, anemia exacerbates the mismatch between myocardial oxygen supply and demand by reducing oxygen-carrying capacity and simultaneously increasing myocardial consumption through increased cardiac output ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“… 2 3 For instance, former studies have shown that preoperative anaemia is associated with an increased risk of post-TAVI mortality and adverse clinical outcomes. 4 5 …”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been undertaken to understand the prognostic value of different comorbidities and biomarkers on TAVI outcomes 2 3. For instance, former studies have shown that preoperative anaemia is associated with an increased risk of post-TAVI mortality and adverse clinical outcomes 4 5…”
Section: Introductionmentioning
confidence: 99%